2019 cultural and creative industries monitoring report. Summary - Raphaela Andres; Daniel Erdsiek; Jörg Ohnemus; Christian Rammer; Steffen Viete (Federal Ministry for Economic Affairs and Energy (BMWi), 2019)
On behalf of the Federal Ministry for Economic Affairs and Energy, the Centre for European Economic Research (ZEW) in Mannheim and the Fraunhofer Institute for Systems and Innovation Research ISI in Karlsruhe undertake continual research into the cultural and creative industries (CCI) in Germany. The results of this work appear in an annual monitoring report that presents key economic indicators on the cultural and creative industries. The analyses contained in the report are based on data from publicly available sources, data held by ZEW, and from a survey on the cultural and creative industries sector in Germany conducted by ZEW specifically for this project. This summary of the report presents the key results for the project year 2019. [...]
Keywords: 330